Method for producing zeolite using quaternary ammonium salt with hydroxycyclohexyl group, and zeolite obtained by that production method
Patent Information
- Application Number
- JP2023124871
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-31
- Publication Date
- 2025-02-13
AI Technical Summary
【0008】 本開示により、ヒドロキシシクロヘキシル基を有する新規な四級アンモニウム塩を使用するゼオライトの製造方法、及びこれにより得られるゼオライト、の少なくともいずれかを提供することができる。
Smart Images

Figure 2025021133000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a method for producing a zeolite using a quaternary ammonium salt having a hydroxycyclohexyl group, and a zeolite obtained thereby. [Background technology]
[0002] Zeolite may be used as a nitrogen oxide reduction catalyst. One example of a zeolite suitable for a nitrogen oxide reduction catalyst is CHA-type zeolite. In the synthesis of CHA-type zeolite, an organic structure directing agent (hereinafter also referred to as "SDA") is generally used, and examples of the synthesis of CHA-type zeolite using various SDAs have been reported.
[0003] Patent Document 1 describes a quaternary ammonium salt compound having a hydroxycyclohexyl group, and describes the use of this compound as a catalyst for the production of silicone resin. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] British Patent No. 848373 Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present disclosure is to provide at least one of a method for producing a zeolite using a novel quaternary ammonium salt having a hydroxycyclohexyl group, and a zeolite obtained thereby. [Means for solving the problem]
[0006] The inventors have discovered that a quaternary ammonium salt represented by the following general formula (1) acts as a source of an organic structure directing agent for producing zeolite, and have completed the invention according to the present disclosure.
[0007] That is, the present invention is as set forth in the claims, and the gist of the present disclosure is as follows. [1] A method for producing a zeolite, comprising: a crystallization step of crystallizing a composition containing a quaternary ammonium salt represented by general formula (1), a silica source, an alumina source, an alkali source, and water. [ka] [In general formula (1), R 1 and R 2 each independently represents a methyl group, an ethyl group, a normal propyl group, or an isopropyl group; Y - represents a halide ion or a hydroxide ion. [2] R in the general formula (1) 1 and R 2 are each independently a methyl group or an ethyl group. [3] R in the general formula (1) 1 and R 2 The method for producing a zeolite according to the above [1] or [2], wherein is a methyl group. [4] Y in the general formula (1) - But Cl - (chloride ion), Br - (bromide ion), I - (iodide ion), or OH - (hydroxide ion), [5] A method for producing a zeolite according to any one of [1] to [4] above, wherein the zeolite has at least the following powder X-ray diffraction peaks in its powder X-ray diffraction pattern: [Table 1] [6] The method for producing a zeolite according to the above [5], wherein the zeolite is a CHA-type zeolite. [7] A zeolite having at least the following powder X-ray diffraction peaks in its powder X-ray diffraction pattern: [Table 2] [8] The zeolite according to [7] above, wherein the zeolite is a CHA-type zeolite. [9] The zeolite according to [7] or [8] above, wherein the molar ratio of silica to alumina is 11 or more and 18 or less.
[10] A nitrogen oxide reduction catalyst comprising the zeolite according to any one of [7] to [9] above. Effect of the Invention
[0008] The present disclosure can provide at least one of a method for producing a zeolite using a novel quaternary ammonium salt having a hydroxycyclohexyl group, and a zeolite obtained thereby. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a diagram showing the 1H-NMR spectrum of trans-4-hydroxy-N,N,N-trimethylcyclohexanaminium iodide of Synthesis Example 2-1. [Diagram 2] FIG. 2 is a diagram showing the XRD pattern of the zeolite of Example 1-1. [Diagram 3] FIG. 3 is an SEM image of the zeolite of Example 1-1. [Figure 4] FIG. 4 is a diagram showing the XRD pattern of the zeolite of Example 1-2. [Diagram 5] FIG. 5 is an SEM image of the zeolite of Example 1-2. [Figure 6] FIG. 6 is a diagram showing an XRD pattern of Comparative Example 1-1. [Figure 7] FIG. 7 is a graph showing the relationship between the temperature of the treatment gas and the nitrogen oxide reduction rate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, the present disclosure will be described with reference to an example of an embodiment.
[0011] First, the definitions of the terms used in this embodiment will be explained in detail.
[0012] "Zeolite" is a compound in which the skeleton atoms (hereinafter also referred to as "T atoms") have a regular structure with oxygen (O) interposed therebetween, and the T atoms are at least one of metal atoms and metalloid atoms. The metal atoms include at least one selected from the group consisting of aluminum (Al), titanium (Ti), iron (Fe), zinc (Zn), gallium (Ga) and tin (Sn), and aluminum is preferred. The metalloid atoms include at least one selected from the group consisting of boron (B), silicon (Si), germanium (Ge), arsenic (As), antimony (Sb) and tellurium (Te), and silicon is preferred.
[0013] A "zeolite-like substance" is a compound having a regular structure in which T atoms are oxygen-mediated, and which contains at least an atom other than a metal atom and a metalloid atom (hereinafter also referred to as a "nonmetal atom") as the T atom. As an example, a zeolite-like substance contains a metal atom and a nonmetal atom as the T atom. Specific examples of zeolite-like substances include complex phosphorus compounds containing phosphorus (P) as the T atom, such as aluminophosphate (AlPO) and silicoaluminophosphate (SAPO). "Zeolite-like substances" are distinguished from "zeolites" in which the T atom is composed of at least one of a metal atom and a metalloid atom.
[0014] An "aluminosilicate" is a complex oxide having a structure consisting of a repeating network of aluminum (Al) and silicon (Si) via oxygen (O). Among aluminosilicates, those that have a crystalline XRD peak in their powder X-ray diffraction (hereinafter also referred to as "XRD") pattern are "crystalline aluminosilicates", and those that do not have a crystalline XRD peak are "amorphous aluminosilicates". Zeolites whose T atoms are composed of aluminum (Al) and silicon (Si) are classified as crystalline aluminosilicates.
[0015] The XRD pattern in this embodiment is measured using CuKα radiation as a radiation source, and the measurement conditions include the following conditions. Acceleration current / voltage: 40mA / 40kV Radiation source: CuKα radiation (λ=1.5405Å) Measurement mode: Continuous scan Scan condition: 40° / min Measurement range: 2θ=3° to 43° Divergence vertical limit slit: 10mm Divergence / entrance slit: 1° Receiving slit: open Receiving solar slit: 5° Detector: Semiconductor detector (D / teX Ultra) Filter: Ni filter
[0016] The crystalline XRD peak is a peak that is detected by identifying the 2θ of the peak top in the analysis of the XRD pattern using a general analysis software (e.g., SmartLab StudioII, manufactured by Rigaku Corporation). Although not particularly limited, the half-width (full width at half maximum) of the XRD peak can be exemplified as 2θ=0.50° or less. The following conditions can be given as the analysis conditions of the XRD pattern. Fitting conditions: Automatic, refine background Dispersive pseudo-Voigt function (peak shape) Background removal method: Fitting method Kα2 removal method: Kα1 / Kα2 ratio=0.497 Smoothing method: B-Spline curve Smoothing conditions: second-order differential method, σ cut value = 3, χ threshold = 1.5
[0017] The XRD pattern can be measured using a general powder X-ray diffraction device (eg, Ultima IV Protectus, manufactured by Rigaku).
[0018] The "ordered structure" of zeolite and zeolite-like substances refers to a skeletal structure that has a skeletal structure specified by the structure code (hereinafter simply referred to as "structure code") established by the Structure Commission of the International Zeolite Association (hereinafter also referred to as "IZA") and an intergrowth structure described on the IZA homepage "http: / / www.iza-struture.org / databases / ". For example, CHA-type zeolite is a skeletal structure specified by the structure code "CHA". The skeletal structure (structure code) and intergrowth structure of each zeolite can be identified by, for example, comparison with the XRD pattern (hereinafter also referred to as "reference pattern") of each structure described in Collection of simulated XRD powder patterns for zeolites, Fifth revised edition (2007). With respect to the skeletal structure, the terms skeletal structure, crystal structure, and crystal phase are used interchangeably.
[0019] In this embodiment, "CHA type zeolite", such as "CHA type zeolite", means a zeolite having a skeletal structure of the structure code, preferably means a zeolite having only the skeletal structure of the structure code, and more preferably means a crystalline aluminosilicate having the skeletal structure of the structure code.
[0020] The composition in this embodiment, such as the molar ratio of silica to alumina, may be measured by ICP analysis using a general inductively coupled plasma optical emission spectrometer (e.g., OPTIMA3300DV, manufactured by PERKIN ELMER). For the measurement using an inductively coupled plasma optical emission spectrometer, a measurement solution in which a sample is dissolved in a mixed solution of hydrofluoric acid and nitric acid can be used.
[0021] Hereinafter, one embodiment of the present disclosure will be described.
[0022] The production method of this embodiment is a zeolite production method including a crystallization step of crystallizing a composition containing a quaternary ammonium salt represented by the following general formula (1) (hereinafter also referred to as "quaternary ammonium salt (1)"), a silica source, an alumina source, an alkali source, and water (hereinafter also referred to as "raw material composition"). [ka] [In general formula (1), R 1 and R 2 each independently represents a methyl group, an ethyl group, a normal propyl group, or an isopropyl group; Y - represents a halide ion or a hydroxide ion.
[0023] In the quaternary ammonium salt (1) contained in the raw material composition, R 1 and R 2 From the viewpoint of preventing the formation of a zeolite having a structure other than the intended one, it is preferable that each of the groups is independently a methyl group or an ethyl group, and it is more preferable that each of the groups is a methyl group.
[0024] In the quaternary ammonium salt (1) contained in the raw material composition, Y in the general formula (1) - From the viewpoint that it is difficult to generate zeolite with a structure other than the intended one, - (chloride ion), Br - (bromide ion), I - (iodide ion), or OH - (hydroxide ion), preferably OH -(hydroxide ion) is more preferable.
[0025] Among the quaternary ammonium salts (1), the quaternary ammonium salt (1) contained in the raw material composition is represented by the general formula (1), 1 and R 2 are all methyl groups, and Y in the general formula (1) - Cl - (chloride ion), Br - (bromide ion), I - (iodide ion), or OH - Such a particularly preferable quaternary ammonium salt (1) can be represented by any one of the following chemical formulas (1-1) to (1-4). [ka]
[0026] The silica source contained in the raw material composition is a compound containing silica (SiO2) or a silicon precursor thereof. Specific examples of the silica source include at least one selected from the group consisting of colloidal silica, amorphous silica, sodium silicate, tetraethyl orthosilicate, precipitated silica, fumed silica, crystalline aluminosilicate, and amorphous aluminosilicate, and preferably at least one selected from the group consisting of crystalline aluminosilicate, amorphous aluminosilicate, and sodium silicate.
[0027] The alumina source contained in the raw material composition is a compound containing alumina (Al2O3) or its precursor aluminum. Specific examples of the alumina source include at least one selected from the group consisting of aluminum sulfate, sodium aluminate, aluminum hydroxide, aluminum chloride, amorphous aluminosilicate, crystalline aluminosilicate, and metallic aluminum, and preferably at least one selected from the group consisting of aluminum sulfate, crystalline aluminosilicate, and amorphous aluminosilicate. In addition, substances containing aluminum (Al) and silicon (Si), such as amorphous aluminosilicate and crystalline aluminosilicate, can be used not only as an alumina source but also as the above-mentioned silica source.
[0028] The raw material composition contains a quaternary ammonium salt (1) as an SDA source. The quaternary ammonium cation having a hydroxycyclohexyl group contained in the quaternary ammonium salt (1) functions as an SDA directed toward a zeolite (e.g., a CHA-type zeolite).
[0029] The raw material composition may contain only the quaternary ammonium salt (1) as the SDA source, but may also contain an organic structure-directing agent source other than the quaternary ammonium salt (1) (hereinafter also referred to as "other organic structure-directing agent source"). As the other organic structure-directing agent source, a known SDA or a salt thereof that directs the framework structure of the zeolite to be produced by the production method of this embodiment can be used. For example, known SDAs that direct CHA-type zeolite can include one or more selected from the group of trialkyladamantan ammonium cation, trialkylcyclohexyl ammonium cation, and quinuclidine cation. When a salt of SDA is used as the other organic structure-directing agent source, it can be used in the form of one or more salts selected from the group of hydroxide, chloride, bromide, and iodide.
[0030] The alkali source contained in the raw material composition may be a compound containing an alkali metal element, and may be at least one of an alkali metal hydroxide and an alkali metal halide. Specific examples of the alkali metal include at least one selected from the group consisting of sodium, potassium, rubidium, and cesium, and is preferably at least one of sodium and potassium, or sodium.
[0031] The water contained in the raw material composition may be, for example, pure water. Note that water contained as a solvent or structural water in other starting materials such as a silica source may be regarded as water contained in the raw material composition.
[0032] The molar ratio of silica to alumina in the raw material composition (hereinafter also referred to as "SiO2 / Al2O3") is preferably 5 or more, 7 or more, or 10 or more, and preferably 100 or less, 50 or less, or 30 or less. The combination of the upper and lower limits of the above-mentioned SiO2 / Al2O3 is arbitrary, but the range of SiO2 / Al2O3 in the raw material composition is preferably 5 or more and 100 or less, 7 or more and 50 or less, or 10 or more and 30 or less.
[0033] The molar ratio of SDA to silica in the raw material composition (hereinafter also referred to as "SDA / SiO2") is preferably 0.01 or more, 0.06 or more, or 0.10 or more, and preferably 2.0 or less, 0.50 or less, or 0.30 or less. The combination of the upper and lower limits of the above-mentioned SDA / SiO2 is arbitrary, but the range of SDA / SiO2 in the raw material composition is preferably 0.01 or more and 2.0 or less, 0.06 or more and 0.50 or less, or 0.10 or more and 0.30 or less. The SDA in the raw material composition is trans-4-hydroxy-N,N,N-trimethylcyclohexanaminium cation (hereinafter "HTMC + ").
[0034] The molar ratio of alkali metal to silica in the raw material composition (hereinafter also referred to as "M / SiO2") is preferably 0.06 or more, 0.10 or more, or 0.15 or more, and preferably 1.0 or less, 0.70 or less, or 0.50 or less. The combination of the upper and lower limits of the above-mentioned M / SiO2 is arbitrary, but the range of M / SiO2 in the raw material composition is preferably 0.06 or more and 1.0 or less, 0.10 or more and 0.70 or less, or 0.15 or more and 0.50 or less. Note that M / SiO 2に In the formula, M is the total molar amount of alkali metals, and when the alkali metal is sodium, or when the alkali metals are sodium and potassium, M / SiO2 is Na / SiO2 or (Na+K) / SiO2, respectively.
[0035] The molar ratio of hydroxide ions to silica in the raw material composition (hereinafter also referred to as "OH / SiO2") is preferably 0.10 or more, 0.15 or more, 0.20 or more, or 0.25 or more, and preferably 1.0 or less, 0.80 or less, or 0.70 or less. The combination of the upper and lower limits of the above-mentioned OH / SiO2 is arbitrary, but the range of OH / SiO2 in the raw material composition is preferably 0.10 or more and 1.0 or less, 0.15 or more and 0.80 or less, 0.20 or more and 0.70 or less, or 0.25 or more and 0.70 or less.
[0036] The molar ratio of water to silica in the raw material composition (hereinafter also referred to as "H2O / SiO2") is preferably 5 or more, 6 or more, or 7 or more, and preferably 60 or less, 30 or less, or 20 or less. The combination of the upper and lower limits of H2O / SiO2 described above is arbitrary, but the range of H2O / SiO2 in the raw material composition is preferably 5 or more and 60 or less, 6 or more and 30 or less, or 7 or more and 20 or less.
[0037] In this embodiment, the raw material composition preferably has any combination of the following compositions. SiO2 / Al2O3: 5 or more, 7 or more, or 10 or more, and 100 or less, 50 or less, or 30 or less SDA / SiO2: 0.01 or more, 0.06 or more, or 0.10 or more, and 2.0 or less, 0.50 or less, or 0.30 or less M / SiO2: 0.06 or more, 0.10 or more, or 0.15 or more, and 1.0 or less, 0.70 or less, or 0.50 or less OH / SiO2: 0.10 or more, 0.15 or more, 0.20 or more, or 0.25 or more, and 1.0 or less, 0.80 or less, or 0.70 or less H2O / SiO2: 5 or more, 6 or more, or 7 or more, and 60 or less, 30 or less, or 20 or less
[0038] In the crystallization step, the raw material composition may be crystallized in the presence of seed crystals. When the raw material composition is crystallized in the presence of seed crystals, the amount of seed crystals may be, for example, more than 0 mass% or 0.5 mass% or more, and may be 10.0 mass% or less, 5.0 mass% or less, or 3.5 mass% or less, as a mass ratio of silicon in the seed crystals converted into silica to the mass of silicon in the raw material composition (not including seed crystals) converted into silica (SiO2). The combination of the upper and lower limits of the above-mentioned seed crystal amount is arbitrary, but the range of the seed crystal amount may be, for example, more than 0 mass% and 10.0 mass% or less, more than 0 mass% and 5.0 mass% or less, or 0.5 mass% or more and 3.5 mass% or less, as a mass ratio of silicon in the seed crystals converted into silica to the mass of silicon in the raw material composition (not including seed crystals) converted into silica (SiO2).
[0039] The seed crystal can be a zeolite according to the skeletal structure of the zeolite to be produced by the production method of this embodiment. For example, when producing a CHA type zeolite, the seed crystal may be a zeolite that does not contain an odd-numbered ring in the crystal structure, and is preferably one or more zeolites having any of the skeletal structures selected from the group consisting of FAU type, CHA type, AEI type, LEV type, AFX type, ERI type, OFF type, LTL type, and GME type, more preferably one or more zeolites having any of the skeletal structures selected from the group consisting of CHA type, AEI type, LEV type, AFX type, and ERI type, and even more preferably CHA type zeolite.
[0040] In the present embodiment, the crystallization step crystallizes the raw material composition. The crystallization may be performed, for example, by subjecting the raw material composition to hydrothermal treatment. The hydrothermal treatment may be performed by placing the raw material composition in a sealed pressure-resistant container and heating it. Examples of the hydrothermal treatment conditions include the following conditions. Treatment temperature: 80°C or higher or 140°C or higher, and 190°C or lower or 180°C or lower Processing time: 2 to 500 hours Processing pressure: Natural pressure
[0041] The state of the raw material composition during crystallization is not limited, and may be either still or stirred, but is preferably stirred.
[0042] The zeolite production method of the present embodiment may include, in addition to the above-mentioned crystallization step, a post-treatment step such as a washing step, a drying step, an SDA removal step, or an ammonium treatment step.
[0043] In the washing step, the zeolite obtained in the crystallization step is washed. Any method for washing may be used, but a method for washing the zeolite may be, for example, contacting the zeolite with a sufficient amount of pure water.
[0044] The drying step removes moisture from the zeolite obtained in the crystallization step or from the washed zeolite. Any drying method may be used, but an example of the drying method is treating the zeolite in air at 100°C or higher and 150°C or lower for 2 hours or more. The upper limit of the drying time is not particularly limited, but can be, for example, 24 hours or less.
[0045] In the SDA removal step, SDA remaining in the crystallized zeolite, the washed zeolite, or the dried zeolite is removed. The SDA removal method may be at least one selected from the group consisting of a liquid phase treatment using an acidic aqueous solution, an exchange treatment using a resin, or the like, and a heat treatment (thermal decomposition). From the viewpoint of production efficiency, the SDA removal treatment is preferably a heat treatment (thermal decomposition), and examples of the heat treatment conditions include treatment in the air at 400° C. to 700° C. for 1 hour to 2 hours.
[0046] In the ammonium treatment step, alkali metals are removed from the crystallized zeolite, the washed zeolite, the dried zeolite, or the SDA-removed zeolite, and the cation type is changed to the ammonium type (hereinafter referred to as "NH 4+ The ammonium treatment method includes contacting the zeolite with an aqueous solution containing ammonium ions. 4+ The zeolite of the cation type was heat-treated to change to the proton type (hereinafter referred to as "H + Zeolite of the "NH type" may also be used. 4+ Specific heat treatment conditions for converting a zeolite of the proton type to a zeolite of the proton type include treatment in air at 500°C or higher for 1 hour to 2 hours. The upper limit of the heat treatment temperature is not particularly limited, but can be, for example, 900°C or lower.
[0047] According to the manufacturing method of the present embodiment described above, zeolite can be manufactured. As an example of the zeolite manufactured by the manufacturing method of the present embodiment (hereinafter, also referred to as "zeolite of the present embodiment"), CHA type zeolite can be exemplified. Note that the zeolite manufactured by the manufacturing method of the present embodiment is not limited to CHA type zeolite, and may be a zeolite having a crystal structure other than CHA type zeolite. For example, in the crystallization step in the manufacturing method of the present embodiment, a zeolite having a crystal structure other than CHA type zeolite can be manufactured by changing the composition of the raw material composition, changing the crystallization conditions of the raw material composition, changing the type of other organic structure directing agent source contained in the raw material composition, or changing the type of seed crystal added to the raw material composition. As an example of a zeolite having a crystal structure other than CHA type zeolite, a small pore zeolite other than CHA type, that is, a zeolite having a crystal structure in which the maximum pore is an 8-membered oxygen ring or less, can be exemplified.
[0048] Next, a method for producing the quaternary ammonium salt (1) contained in the raw material composition will be described.
[0049] The quaternary ammonium salt (1) can be produced by a production method including a step of reacting a compound represented by the following general formula (2) (hereinafter also referred to as "compound (2)") with a compound represented by the following general formula (3) (hereinafter also referred to as "compound (3)") (hereinafter also referred to as "reaction step").
[0050] [ka] [In general formula (2), R 1 represents a methyl group, an ethyl group, a normal propyl group, or an isopropyl group.
[0051] [ka] [In general formula (2), R 2represents a methyl group, an ethyl group, a normal propyl group, or an isopropyl group, and Y represents a halogen atom or a hydroxy group.
[0052] In the compound (2) used in the reaction step, R 1 From the viewpoint of preventing the formation of a zeolite having a structure other than the intended one, is preferably a methyl group or an ethyl group, and more preferably a methyl group.
[0053] The compound (2) used in the reaction step may be a commercially available product as is, or may be synthesized by alkylating commercially available 4-aminocyclohexanol by a known method, as shown in Synthesis Example 1 described later.
[0054] In the compound (3) used in the reaction step, R 2 From the viewpoint of preventing the formation of a zeolite having a structure other than the intended one, is preferably a methyl group or an ethyl group, and more preferably a methyl group.
[0055] In the compound (3) used in the reaction step, Y in the general formula (3) is preferably Cl (chlorine atom), Br (bromine atom), I (iodine atom) or OH (hydroxy group), more preferably OH (hydroxy group), from the viewpoint of preventing the production of a zeolite having a structure other than the target.
[0056] Among the compounds (3), the compound (3) used in the reaction step is represented by the general formula (3) R 2 are all methyl groups, and Y in general formula (3) is particularly preferably Cl (chlorine atom), Br (bromine atom), I (iodine atom), or OH (hydroxy group).
[0057] The compound (3) used in the reaction step may be a commercially available product.
[0058] The reaction between compound (2) and compound (3) in the reaction step can be represented by the following reaction formula (I): As shown in reaction formula (I), the quaternary ammonium salt (1) is obtained by reacting compound (2) with compound (3) in the reaction step. [ka]
[0059] The amount of compound (3) used in the reaction step is preferably 2 moles or more, and preferably 100 moles or less, or 10 moles or less, relative to 1 mole of compound (2) in terms of excellent reaction yield. The combination of the upper and lower limits of the amount of compound (3) described above is arbitrary, but the range of the amount of compound (3) used in the reaction step is preferably 2 moles or more and 100 moles or less, and more preferably 2 moles or more and 10 moles or less, relative to 1 mole of compound (2).
[0060] The reaction of compound (2) and compound (3) in the reaction step is not particularly limited as long as the reaction represented by the above reaction formula (I) proceeds, but it is preferable to react compound (2) and compound (3) in a solvent.
[0061] The solvent that can be used in the reaction of compound (2) and compound (3) is not limited as long as it does not inhibit the reaction represented by the above reaction formula (I). For example, one or more solvents selected from the group consisting of aromatic hydrocarbon solvents, ether solvents, ester solvents, halogen solvents, amide solvents, ketone solvents, nitrile solvents, sulfoxide solvents, alcohol solvents, and water can be mentioned.
[0062] More specific examples of the solvent include aromatic hydrocarbon solvents such as at least one of toluene and xylene, ether solvents such as at least one selected from the group consisting of tetrahydrofuran, 1,2-dimethoxyethane, and 1,4-dioxane, ester solvents such as ethyl acetate or butyl acetate, halogen solvents such as at least one of dichloromethane, chloroform, carbon tetrachloride, and chlorobenzene, amide solvents such as at least one of N,N-dimethylformamide and N,N-dimethylacetamide, ketone solvents such as at least one of acetone and methyl ethyl ketone, nitrile solvents such as at least one selected from the group consisting of acetonitrile, propionitrile, and benzonitrile, sulfoxide solvents such as dimethyl sulfoxide, and alcohol solvents such as at least one selected from the group consisting of methanol, ethanol, and propanol.
[0063] The solvent that can be used in the reaction of compound (2) and compound (3) is preferably at least one of a halogen-based solvent and an alcohol-based solvent, and more preferably at least one selected from the group consisting of dichloromethane, ethanol, and methanol.
[0064] The reaction temperature in the reaction step may be any temperature at which the reaction between compound (2) and compound (3) proceeds, and is preferably from 0°C to 200°C, more preferably from 20°C to 80°C.
[0065] The reaction time in the reaction step may be appropriately adjusted depending on the reaction temperature and the amounts of compound (2) and compound (3) to be reacted, but is preferably from 1 hour to 100 hours.
[0066] In the reaction step, a specific example of a method for reacting compound (2) with compound (3) is a method of heating a reaction liquid containing compound (2), compound (3), and a solvent.
[0067] The method for producing the quaternary ammonium salt (1) may include, in addition to the reaction step described above, a step of isolating the quaternary ammonium salt (1) obtained in the reaction step (hereinafter also referred to as an "isolation step"), and a step of ion-exchanging the quaternary ammonium salt (1) obtained in the reaction step or the isolation step (hereinafter also referred to as an "ion exchange step").
[0068] The isolation method in the isolation step may be any method capable of isolating the quaternary ammonium salt (1) from the reaction mixture, and may be any purification method commonly used by those skilled in the art. Specific examples of the isolation method include one or more methods selected from the group consisting of solvent extraction, column chromatography, preparative thin-layer chromatography, preparative liquid chromatography, and recrystallization.
[0069] In the ion exchange process, the ion Y contained in the quaternary ammonium salt (1) - and a different type of ion Y - (halide ions, or hydroxide ions) are exchanged.
[0070] The ion exchange method in the ion exchange step can be a general method used by those skilled in the art for ion exchange of quaternary ammonium salts. A specific ion exchange method, for example, is to contact the quaternary ammonium salt (1) with an ion exchange resin. The ion exchange resin is used to ionize the ion Y contained in the quaternary ammonium salt (1) to be ion exchanged. - A different type of exchange group Y - For example, one or more selected from the group consisting of Diaion SA10A, Diaion SA12A, and Diaion SA11A can be used, and among these, Diaion SA10A is more preferable.
[0071] The ion exchange of the quaternary ammonium salt (1) can be carried out in a solvent that does not inhibit the ion exchange. For example, the ion exchange can be carried out by contacting a mixed solution containing the quaternary ammonium salt (1) and a solvent with an ion exchange resin. Examples of the solvent that can be used for the ion exchange include one or more selected from the group consisting of ether solvents, ester solvents, ketone solvents, nitrile solvents, alcohol solvents, and water. Specific examples of the ether solvents, ester solvents, ketone solvents, nitrile solvents, and alcohol solvents are the same as those that can be used for the reaction of compound (2) and compound (3), so the explanation will be omitted.
[0072] Next, the zeolite produced by the production method of this embodiment (hereinafter also referred to as "the zeolite of this embodiment") will be described.
[0073] The zeolite of this embodiment has at least the XRD peaks in the XRD pattern shown in Table 3 below. The zeolite of this embodiment has the XRD peaks in Table 3 below that are not observed in conventional zeolites, and therefore can exhibit excellent hydrothermal durability. The inventors named the zeolite of this embodiment ZTS-9. [Table 3]
[0074] In this embodiment, "having an XRD peak shown in the table" means that a peak having a relative peak intensity shown in the table can be confirmed in the XRD pattern within the range of lattice spacing d (Å) shown in the table. Also, "being able to confirm a peak within the range of lattice spacing d (Å) shown in the table" means that a peak having a peak top within the range of lattice spacing d (Å) can be confirmed.
[0075] The zeolite of this embodiment may contain XRD peaks with a relative peak intensity of less than 5% in its XRD pattern, and such XRD peaks do not need to be taken into consideration in identifying the zeolite framework structure.
[0076] The zeolite of the present embodiment may have at least the XRD peaks shown in Table 3 in its XRD pattern, and may further include XRD peaks (hereinafter also referred to as "other XRD peaks") other than the XRD peaks shown in Table 3. The zeolite of the present embodiment preferably has the XRD peaks shown in Table 4 below, among those further including such other XRD peaks.
[0077] [Table 4]
[0078] The zeolite of this embodiment is not limited in terms of its crystal structure as long as it has at least the XRD peaks shown in Table 3, but can be exemplified as a zeolite having a crystal structure in which the largest pore has an oxygen ring of 8 members or less. From the viewpoint of applying the zeolite of this embodiment to a nitrogen oxide reduction catalyst, the zeolite of this embodiment is preferably a CHA-type zeolite.
[0079] In order to make the zeolite of the present embodiment more applicable to nitrogen oxide reduction catalysts, the molar ratio of silica to alumina (hereinafter also referred to as "SiO2 / Al2O3 ratio") is preferably 5 or more, 7 or more, 8 or more, or 11 or more, and preferably 50 or less, 30 or less, 18 or less, or 15 or less. The combination of the upper and lower limits of the SiO2 / Al2O3 ratio described above is arbitrary, but the range of the SiO2 / Al2O3 ratio of the zeolite of the present embodiment is preferably 5 or more and 50 or less, 7 or more and 30 or less, 8 or more and 18 or less, 11 or more and 18 or less, or 11 or more and 15 or less. In general, the higher the SiO2 / Al2O3 ratio, the higher the heat resistance of the zeolite tends to be, but the zeolite of the present embodiment can exhibit excellent hydrothermal durability even if it has a low silica composition, such as a SiO2 / Al2O3 ratio of 13 or less, or even 10 or less.
[0080] The zeolite of this embodiment has a molar ratio of the total amount of alkali metals to aluminum (hereinafter also referred to as "M / Al ratio", where "M" is the total molar amount of alkali metals contained in the zeolite) of, for example, 0.2 or more, or 0.3 or more, and 0.9 or less, or 0.7 or less. The combination of the upper and lower limits of the M / Al ratio described above is arbitrary, but the range of the M / Al ratio in the zeolite of this embodiment is 0.2 or more and 0.9 or less, and preferably 0.3 or more and 0.7 or less.
[0081] The zeolite of this embodiment may be either crystal particles formed by primary particles or crystal particles (aggregates) formed by chemically agglomerating primary particles together, or may be both. The crystal particles in the zeolite of this embodiment are not particularly limited, but may be at least one selected from the group consisting of crystal particles having a shape of either a rhombohedron or a cube (a hexahedron with all sides of equal length), polyhedral crystal particles including some faces constituting a rhombohedron or a cube, and amorphous crystal particles. The crystal particles in the zeolite of this embodiment are not limited to the crystal particles of the above-mentioned form, and may be, for example, amorphous crystal particles close to a sphere, or even approximately spherical crystal particles.
[0082] The average crystal particle size of the zeolite of this embodiment is preferably 0.1 μm or more, or 0.15 μm or more, and preferably 2.0 μm or less, or 1.5 μm or less, because this makes it easier to apply the zeolite to nitrogen oxide reduction catalysts. The combination of the upper and lower limits of the average particle size described above is arbitrary, but the average crystal particle size of the zeolite of this embodiment is preferably 0.1 μm or more and 2.0 μm or less, and more preferably 0.15 μm or more and 1.5 μm or less.
[0083] In this embodiment, the average crystal grain size means the average value of the particle diameter of the primary particles. The primary particles are the smallest unit particles that can be observed independently in scanning electron microscope (hereinafter also referred to as "SEM") observation under the following conditions. The SEM observation may be performed using a general scanning electron microscope (for example, device name: JSM-IT200, manufactured by JEOL Ltd.). The average crystal grain size may be determined by first randomly extracting 100±10 primary particles whose contours are observed without interruption in the SEM observation image, measuring the longest diameter of each extracted primary particle, and calculating the average value, which is the average crystal grain size. The number of SEM observation images may be any number that allows the above-mentioned number of primary particles to be observed, and one or more SEM observation images may be used. Acceleration voltage: 5kV Magnification: 10,000±5,000x
[0084] The zeolite of the present embodiment is preferably free of fluorine (F) and phosphorus (P) in view of reducing the environmental load, omitting removal equipment, and producing it at low cost. Free of fluorine and phosphorus means that the respective substances cannot be detected (below the measurement limit). Depending on the detection capability of the detection device, for example, it can be determined that the fluorine content is 1 ppm or less and that the phosphorus content is 1 ppm or less and that the phosphorus content is 1 ppm or less. In addition, for example, it can be determined that the phosphorus and fluorine content is not contained when the sum of the fluorine content and the phosphorus content is 1 ppm or less.
[0085] The zeolite of the present embodiment can be applied to known uses of zeolites, and can be used for applications such as adsorbents, catalysts, adsorbent carriers, catalyst carriers, etc. In particular, the zeolite of the present embodiment exhibits excellent hydrothermal durability, and is therefore suitable for nitrogen oxide reduction catalysts, SCR catalysts, or carriers thereof.
[0086] When the zeolite of this embodiment is used for the above-mentioned purposes, it may be used as it is, or may be used after containing an active metal element according to the purpose of use. The active metal element contained in the zeolite of this embodiment is preferably one or more selected from the group consisting of platinum (Pt), palladium (Pd), rhodium (Rh), iron (Fe), copper (Cu), cobalt (Co), nickel (Ni), manganese (Mn) and indium (In), more preferably one or more metal elements selected from the group consisting of cobalt (Co), nickel (Ni), iron (Fe) and copper (Cu), and more preferably at least one of iron and copper, or even more preferably copper.
[0087] The active metal element is preferably contained as a substance other than the T atoms constituting the framework structure of the zeolite of this embodiment, and is preferably contained in a state supported outside the framework of the zeolite of this embodiment, for example, supported in at least one of pores and ion exchange sites.
[0088] In the zeolite of this embodiment, the content of the active metal element is preferably 1.5 mass% or more, 2.0 mass% or more, or 2.5 mass% or more, and preferably 6.5 mass% or less, 6.0 mass% or less, or 5.5 mass% or less, relative to 100 mass% of the zeolite of this embodiment (100 mass% of the zeolite containing the active metal element), from the viewpoint of further improving the catalytic activity. The combination of the upper and lower limits of the content of the active metal element described above is arbitrary, but the range of the content of the active metal element in the zeolite of this embodiment is preferably 1.5 mass% or more and 6.5 mass% or less, 2.0 mass% or more and 6.0 mass% or less, or 2.5 mass% or more and 5.5 mass% or less.
[0089] The method of making the zeolite of the present embodiment contain an active metal element is not particularly limited, and a conventionally known method can be used. For example, a method of permeating the zeolite of the present embodiment with a solution containing a salt of an active metal element (hereinafter also referred to as a "metal salt solution") and calcining the zeolite can be mentioned. Examples of the solvent used for the metal salt solution include at least one of water and alcohol. The calcination conditions of the zeolite permeated with the metal salt solution can be, for example, in the air, at 400°C to 600°C, and for 1 hour to 10 hours. The zeolite permeated with the metal salt solution may be dried before the calcination treatment. The drying method is arbitrary, but for example, the drying method can be in the air, at 60°C to 130°C, and for 0.5 hours to 20 hours. EXAMPLES
[0090] Next, examples of the present embodiment will be described, but the present embodiment is not limited to these.
[0091] ( 1 H-NMR) A JEOL ECZ400 (400MHz, JEOL) was used to measure the 1 H-NMR spectrum was measured. Heavy water (DO) was used as the measurement solvent, and tetramethylsilane (TMS) was used as the internal standard. 1 H-NMR spectrum was measured.
[0092] (Powder X-ray diffraction) The XRD of the sample was measured using a general X-ray diffraction device (device name: UltimaIV Protectus, manufactured by Rigaku Corporation). The measurement conditions were as follows: Acceleration current / voltage: 40mA / 40kV Radiation source: CuKα radiation (λ=1.5405Å) Measurement mode: Continuous scan Scan condition: 40° / min Measurement range: 2θ=3° to 43° Divergence vertical limit slit: 10mm Divergence / entrance slit: 1° Receiving slit: open Receiving solar slit: 5° Detector: Semiconductor detector (D / teX Ultra) Filter: Ni filter
[0093] The XRD patterns obtained as a result of the sample measurements were analyzed using a general analysis software (SmartLab Studio II, Rigaku) under the following conditions to identify the XRD peaks. In addition, the skeletal structure of the sample was identified by comparing the XRD pattern with a reference pattern. Fitting conditions: Automatic, refine background Dispersive pseudo-Voigt function (peak shape) Background removal method: Fitting method Kα2 removal method: Kα1 / Kα2 ratio=0.497 Smoothing method: B-Spline curve Smoothing conditions: second-order differential method, σ cut value = 3, χ threshold = 1.5
[0094] (Composition analysis, quantitative analysis of silicon, aluminum, sodium, and copper) The composition of the samples was analyzed using a general inductively coupled plasma optical emission spectrometer (instrument name: OPTIMA3300DV, manufactured by PERKIN ELMER). The samples were dissolved in a mixed solution of hydrofluoric acid and nitric acid to prepare a measurement solution. The obtained measurement solution was put into the instrument to analyze the composition of the samples. The Na / Al ratio and SiO2 / Al2O3 ratio were calculated from the obtained molar concentrations of silicon (Si), aluminum (Al), and sodium.
[0095] (Measurement of average crystal grain size) Using a general scanning electron microscope (instrument name: JSM-IT200, manufactured by JEOL Ltd.), the measurement sample was observed under the following conditions. 100±10 primary particles whose outlines were observed without interruption in the obtained SEM observation image were randomly selected, the longest diameter of each selected primary particle was measured, and the average value was calculated, which was taken as the average crystal diameter. Acceleration voltage: 5kV Magnification: 10,000±5,000x
[0096] [Synthesis of compound (2)] Synthesis Example 1 [ka] Formaldehyde (38% aqueous solution, 46 g, 0.56 mol) was added to a reaction vessel and cooled to 0°C on ice, trans-4-aminocyclohexanol (Tokyo Chemical Industry Co., Ltd., 25 g, 0.22 mol) was added thereto, and formic acid (98% aqueous solution, 55 g, 1.2 mol) was added dropwise over 30 minutes. After the dropwise addition, the temperature was raised to 85°C and stirred for 24 hours. The obtained reaction liquid was cooled using an ice bath, and a 48% aqueous NaOH solution was added until the pH of the aqueous solution became 11. After extraction with tetrahydrofuran, anhydrous sodium sulfate was added to the extract, and the mixture was stirred, and the solid content was filtered off to obtain a liquid composition. Tetrahydrofuran was removed from the liquid composition using a rotary evaporator, and then distilled under reduced pressure to obtain trans-4-dimethylaminocyclohexanol as a brown oil.
[0097] [Synthesis of quaternary ammonium salts (1)] Synthesis Example 2-1 [ka] A dichloromethane solution (70 mL) of trans-4-dimethylaminocyclohexanol (15.0 g, 0.105 mol) obtained in Synthesis Example 1 was placed in a reaction vessel and cooled to 0°C on ice, and iodomethane (50 g, 0.35 mol) was added dropwise thereto over 30 minutes. After the dropwise addition, the temperature was raised to 50°C and stirred for 24 hours. Next, the reaction solution obtained was cooled using an ice bath, and the white solid precipitated in the reaction solution was filtered off. The filtered product was washed with dichloromethane to obtain a white solid trans-4-hydroxy-N,N,N-trimethylcyclohexanaminium iodide (chemical formula (1-3), purity 99% or more).
[0098] The obtained trans-4-hydroxy-N,N,N-trimethylcyclohexanaminium iodide 1 The H-NMR spectrum (400 MHz, 8 accumulations) is shown in Figure 1.
[0099] Synthesis Example 2-2 [ka] The aqueous solution (40 mL) of trans-4-hydroxy-N,N,N-trimethylcyclohexanaminium iodide (12 g, 0.12 mol) obtained in Synthesis Example 2-1 was diluted with an anion exchange resin (Diaion (registered trademark) SA10A, OH, manufactured by Mitsubishi Chemical Corporation). - The anion exchange resin was separated by filtration, and the mixture was concentrated using a rotary evaporator to obtain a 21% by mass aqueous solution of trans-4-hydroxy-N,N,N-trimethylcyclohexanaminium hydroxide (chemical formula (1-4)) (hereinafter, also referred to as "HTMC-OH").
[0100] [Synthesis of CHA-type zeolite] Example 1-1 A 21% by mass aqueous solution of HTMC-OH, an amorphous aluminosilicate with a SiO2 / Al2O3 ratio of 13.7, 48% sodium hydroxide, and water were mixed to obtain a raw material composition having the following molar composition. Note that SDA in the following composition is HTMC. + It is. SiO2 / Al2O3= 13.7 SDA / SiO2= 0.12 Na / SiO2= 0.18 OH / SiO2= 0.30 H2O / SiO2= 9
[0101] CHA-type zeolite was added and mixed as seed crystals to the obtained raw material composition so that the content was 2.0 mass% (the mass ratio of silicon in the seed crystals converted into silica to the mass of silicon in the raw material composition converted into silica (SiO2)). The raw material composition mixed with the seed crystals was filled into a sealed container and hydrothermally treated at 160°C for 48 hours under autogenous pressure to obtain a crystallized product. The obtained crystallized product was recovered by solid-liquid separation, washed with a sufficient amount of pure water, and dried in the air to obtain the zeolite of this example.
[0102] The zeolite of this example was a single phase CHA type zeolite, with a SiO2 / Al2O3 ratio of 12.1, a Na / Al ratio of 0.39, and an average crystal grain size of 0.28 μm. The XRD pattern of the zeolite of this example (crystallized product after drying) is shown in FIG. 2, and the XRD peaks with a relative peak intensity of 10% or more are shown in Table 5 below. The zeolite of this example was a zeolite having the XRD peaks in Table 3 above, and was confirmed to be ZTS-9. In addition, the SEM observation diagram of the zeolite of this example is shown in FIG. 3. As shown in FIG. 3, the zeolite of this example had a cubic shape and was a crystal grain having a CHA structure. [Table 5]
[0103] Example 1-2 A raw material composition having the following molar composition was obtained in the same manner as in Example 1-1, except that an amorphous aluminosilicate with SiO2 / Al2O3 of 13.0 was used instead of the amorphous aluminosilicate used in Example 1-1. A zeolite of this example was obtained in the same manner as in Example 1-1, except that the raw material composition obtained was used instead of the raw material composition used in Example 1-1. In the following composition, SDA is HTMC. + It is. SiO2 / Al2O3= 13.0 SDA / SiO2= 0.12 Na / SiO2= 0.36 OH / SiO2= 0.48 H2O / SiO2= 14
[0104] The zeolite of this example was a single phase CHA-type zeolite, with a SiO2 / Al2O3 ratio of 10.9, a Na / Al ratio of 0.61, and an average particle size of 0.62 μm. The XRD pattern of the zeolite of this example is shown in Figure 4, the XRD peaks with a relative peak intensity of 10% or more are shown in Table 6 below, and the SEM observation diagram of the CHA-type zeolite of this example is shown in Figure 5. The zeolite of this example was a zeolite having the XRD peaks in Table 3 above, and was confirmed to be ZTS-9. [Table 6]
[0105] Comparative Example 1-1 A raw material composition having the following molar composition was obtained in the same manner as in Example 1-1, except that a 35% by mass aqueous solution of N-ethyl-N,N-dimethylcyclohexylammonium hydroxide was used instead of the 21% by mass aqueous solution of HTMC-OH used in Example 1-1. A zeolite of this comparative example was obtained in the same manner as in Example 1-1, except that the obtained raw material composition was used instead of the raw material composition used in Example 1-1. In the following composition, SDA is N-ethyl-N,N-dimethylcyclohexylammonium cation. SiO2 / Al2O3= 13.7 SDA / SiO2= 0.12 Na / SiO2= 0.18 OH / SiO2= 0.30 H2O / SiO2= 9
[0106] The zeolite of this comparative example was a single phase CHA type zeolite, with a SiO2 / Al2O3 ratio of 11.9, a Na / Al ratio of 0.47, and an average particle size of 0.36 μm. The XRD pattern of the zeolite of this comparative example is shown in FIG. 6, and the XRD peaks with relative peak intensities of 10% or more are shown in Table 7 below. The zeolite of this comparative example did not have the XRD peaks in Table 3 above, and was not ZTS-9. [Table 7]
[0107] [Copper-loaded CHA-type zeolite] Example 2-1 The CHA-type zeolite (ZTS-9) obtained in Example 1-1 was calcined in air at 600°C for 2 hours to remove organic components such as SDA contained in the CHA-type zeolite (ZTS-9). The calcined CHA-type zeolite (ZTS-9) was contacted with a 20% aqueous ammonium chloride solution for 3 minutes, washed, and then dried in air at 110°C overnight to remove sodium contained in the CHA-type zeolite (ZTS-9) and NH 4+ The CHA-type zeolite (ZTS-9) was obtained. 4+ A copper nitrate aqueous solution was dropped onto the CHA-type zeolite (ZTS-9) and mixed in a mortar for 10 minutes. After mixing, the mixture was dried overnight at 110°C in air, and then calcined for 1 hour at 550°C in air to obtain a CHA-type zeolite carrying copper (copper-loaded CHA-type zeolite (copper-loaded ZTS-9)). In the copper-loaded CHA-type zeolite (copper-loaded ZTS-9) of this example, the copper content was 3.0% by mass relative to 100% by mass of the copper-loaded CHA-type zeolite (copper-loaded ZTS-9).
[0108] Comparative Example 2-1 A copper-supported CHA-type zeolite (copper-supported CHA-type zeolite) was obtained in the same manner as in Example 2-1, except that the CHA-type zeolite obtained in Comparative Example 1-1 was used instead of the CHA-type zeolite (ZTS-9) used in Example 2-1. In the copper-supported CHA-type zeolite of this comparative example, the copper content was 3.0% by mass relative to 100% by mass of the copper-supported CHA-type zeolite.
[0109] [Hydrothermal durability treatment] The copper-loaded CHA-type zeolite of Example 2-1 (copper-loaded ZTS-9) and the copper-loaded CHA-type zeolite of Comparative Example 2-1 were molded and crushed to obtain aggregated particles having an aggregate diameter of 12 to 20 mesh. 3 mL of the aggregated particles were packed into an atmospheric pressure fixed-bed flow-type reaction tube (hereinafter also simply referred to as the "reaction tube"), and then subjected to hydrothermal durability treatment under the following conditions. Treatment atmosphere: Air flow atmosphere with a moisture content of 10% by volume Space velocity: 9,000h -1 Processing temperature: 800℃ Processing time: 16 hours
[0110] [Nitrogen oxide reduction test] The nitrogen oxide reduction rate of the samples (copper-loaded CHA-type zeolite (copper-loaded ZTS-9) of Example 2-1 and copper-loaded CHA-type zeolite of Comparative Example 2-1) that had been subjected to hydrothermal durability treatment was measured using the ammonia SCR method. Specifically, 1.5 mL of the sample after hydrothermal durability treatment was packed into a reaction tube, and the treatment gas was passed through the reaction tube under the following conditions, and the nitrogen oxide concentration at the reaction tube outlet was measured. Treatment gas composition: NO 200ppm NH3 200ppm O210 capacity% H2O 3% by volume Remainder N2 Processing gas flow rate: 1.5L / min Space velocity (SV): 60,000hr -1
[0111] Using the measured nitrogen oxide concentration at the outlet of the reaction tube, the nitrogen reduction rate of the sample that had been subjected to hydrothermal durability treatment was calculated according to the following formula (1). Nitrogen oxide reduction rate (%) = {1-([NOx]out / [NOx]in)}×100 ···(1) In the above formula (1), [NOx]out represents the NO concentration at the reaction tube outlet, and [NOx]in represents the NO concentration (200 ppm) in the treatment gas flowing through the reaction tube.
[0112] The relationship between the temperature of the treatment gas circulated through the reaction tube and the nitrogen oxide reduction rate is shown in Table 8 and Figure 7 below. As is clear from Table 8 and Figure 7, the nitrogen reduction rate of the copper-loaded CHA-type zeolite of Example 2-1 (copper-loaded ZTS-9) was equal to or higher than the nitrogen reduction rate of the copper-loaded CHA-type zeolite of Comparative Example 2-1 with the same SiO2 / Al2O3 ratio in the entire temperature range from 150°C to 600°C. From this, it was confirmed that the copper-loaded CHA-type zeolite of Example 2-1 (copper-loaded ZTS-9) has higher nitrogen oxide reduction properties than the copper-loaded CHA-type zeolite of Comparative Example 2-1. [Table 8]
Claims
1. A method for producing a zeolite, comprising: a crystallization step of crystallizing a composition containing a quaternary ammonium salt represented by general formula (1), a silica source, an alumina source, an alkali source, and water. 【Chemistry 1】 [In general formula (1), R 1 and R 2 each independently represents a methyl group, an ethyl group, a normal propyl group, or an isopropyl group; Y - represents a halide ion or a hydroxide ion.
2. R in the general formula (1) 1 and R 2 The method for producing a zeolite according to claim 1 , wherein each of the groups independently represents a methyl group or an ethyl group.
3. R in the general formula (1) 1 and R 2 The method for producing a zeolite according to claim 1 , wherein is a methyl group.
4. Y in the general formula (1) - But Cl - (chloride ion), Br - (bromide ion), I - (iodide ion), or OH - (hydroxide ion) according to claim 1, the method for producing a zeolite.
5. The method for producing a zeolite according to any one of claims 1 to 4, wherein the zeolite has at least the following powder X-ray diffraction peaks in its powder X-ray diffraction pattern: 【Table 1】
6. The method for producing a zeolite according to claim 5, wherein the zeolite is a CHA type zeolite.
7. A zeolite having at least the following powder X-ray diffraction peaks in a powder X-ray diffraction pattern: 【Table 2】
8. 8. The zeolite of claim 7, wherein the zeolite is a CHA type zeolite.
9. 8. The zeolite of claim 7, wherein the molar ratio of silica to alumina is 11 or more and 18 or less.
10. A nitrogen oxide reduction catalyst comprising the zeolite according to any one of claims 7 to 9.
Citation Information
Patent Citations
Organosiloxane compositions
GB848373A